2015
DOI: 10.7314/apjcp.2015.16.5.1813
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Neutrophil/Lymphocyte Ratio in Prediction of PSA Recurrence after Radical Prostatectomy

Abstract: Background: The aim of this study was to research the importance of the neutrophil to lymphocyte ratio (NLR) in prediction of PSA recurrence after radical prostatectomy, which has not been reported so far. Materials and Methods: The data of 175 patients who were diagnosed with localised prostate cancer and underwent retropubic radical prostatectomy was retrospectively examined. Patient pre-operative hemogram parameters of neutrophil count, lymphocyte count and NLR were assessed. The patients whose PSAs were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…However, there is a paucity of studies about the association between NLR and survival outcomes in localized PCa after surgical treatment. Gazel et al [10] recently retrospectively analyzed 175 patients using an NLR cutoff of 2.494 and found that the high-NLR group showed more episodes of recurrence (p < 0.001) and a higher pathological Gleason score (p < 0.001). However, their study included too few subjects and had an ROC that was much higher than those of other studies, which suggests the possibility of hidden bias.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there is a paucity of studies about the association between NLR and survival outcomes in localized PCa after surgical treatment. Gazel et al [10] recently retrospectively analyzed 175 patients using an NLR cutoff of 2.494 and found that the high-NLR group showed more episodes of recurrence (p < 0.001) and a higher pathological Gleason score (p < 0.001). However, their study included too few subjects and had an ROC that was much higher than those of other studies, which suggests the possibility of hidden bias.…”
Section: Discussionmentioning
confidence: 96%
“…Multivariate analysis revealed that high NLR was significantly correlated with adverse pathological outcomes of higher pathological stage (HR 1.688; 95 % CI 1.142-2.497; p = 0.009) and extracapsular extension (HR 1.698; 95 % CI 1.146-2.516; p = 0.008). Kaplan-Meier analysis showed significantly worse BCR-free survival (p < 0.001) in patients with a high increased prostate-specific antigen (PSA) level after radical prostatectomy (RP) [10]. Another study showed a significantly worse prognosis in progression-free, metastasis-free, and overall survival of patients with a high NLR and localized PCa after radiotherapy [11].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, there were only a few studies that investigated the importance of preoperative NLR in prediction of BCR after RP in localized prostate cancer. 15,16 Minardi et al 15 tested the prognostic significance of NLR in the prostate cancer of patients who were candidates for a RP. In that study, they reported that patients with a NLR of 43 had a higher incidence of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 In addition, there were only a few studies that investigated the importance of preoperative NLR in prediction of biochemical recurrence (BCR) after radical prostatectomy (RP) in localized prostate cancer. 15,16 However, the prognostic significance of NLR in terms of survival in patients who have undergone RP for prostate cancer has never been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For castration‐resistant prostate cancer (CRPC), a high NLR is reported to be correlated with poor prognosis . Recent reports have also found that an elevated NLR is associated with early biochemical recurrence (BCR) in patients treated with RP . Another study showed that LPCa patients with high NLRs experience worse prognoses in terms of progression‐free, metastasis‐free, and overall survival after radiotherapy .…”
Section: Introductionmentioning
confidence: 99%